การวิเคราะห์พฤติกรรมการใช้จ่ายเงินของเด็กและเยาวชนที่ติดเกมส์: กรณีศึกษาเยาวชนในพื้นที่จังหวัดเชียงใหม่และลำพูน - บุญยะเสนา พิมลพรรณ; พันธุ์ณรงค์ สุขุม (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2011)
ปัจจุบันปัญหาเรื่องเด็กและเยาวชนติดเกมส์ยิ่งทวีความรุนแรงและมีความซับซ้อนมากยิ่งขึ้น เด็กและเยาวชนได้ใช้จ่ายเพื่อการเล่นเกมส์มากยิ่งขึ้น เด็กและเยาวชนที่ติดเกมส์หลายคนหนีออกจากบ้านเพื่อมาเล่นเกมส์ตามร้านเกมส์ต่างๆ และเสี่ยงต่อการถูกล่อลวงจากแก๊งมิจฉาชีพ ดังนั้นงานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการใช้จ่ายเงินของเด็กและเยาวชนที่ติดเกมส์ รวมถึงปัจจัยกระตุ้นที่ทำให้มีความต้องการใช้จ่ายเงินมากยิ่งขึ้น และเพื่อระดมปัญหาและหาแนวทางในการแก้ไขปัญหาการติดเกมส์และการใช้จ่ายเงิน โดยมีกลุ่มตัวอย่างเป็นเด็ก และเยาวชนที่ติดและไม่ติดเกมส์ อายุระหว่าง 10-22 ปี จำนวน 1,000 คน แบ่งเป็นเด็กและเยาวชนที่ติดเกมส์ 300 คน และเด็กและเยาวชนที่ไม่ติดเกมส์ 700 คน และผู้ปกครอง เจ้าของร้านเกมส์ นักวิชาการ อาจารย์ และหน่วยงานพัฒนาสังคมและมนุษย์ จำนวน 50 คน เก็บข้อมูลจากแบบสัมภาษณ์ วิเคราะห์และแปรผลข้อมูลทางสถิติโดยใช้สถิติเชิงพรรณนาและการทดสอบแบบไคสแควส์ ผลการศึกษาพฤติกรรมการใช้จ่ายเงินของเด็กและเยาวชนที่ติดเกมส์พบว่า เด็กและเยาวชนจะมีรายจ่ายในการเล่นเกมส์ในกรณีต่างๆ แตกต่างกัน เช่น กรณีที่เล่นอยู่ที่บ้าน จะมีรายจ่ายจากค่าต่ออินเทอร์เน็ตบ้าน ประมาณ 500-600 บาทต่อเดือน หรือประมาณ 19 บาทต่อวัน แต่ถ้าเด็กและเยาวชนไม่ได้เล่นที่บ้าน และมาเล่นที่ร้านเกมส์ จะมีรายจ่ายจากการเล่นที่ร้านเกมส์ อาทิเช่น ค่าบริการของร้าน ค่าขนม น้ำอัดลม ค่าบุหรี่ เป็นต้น และนอกนั้นเป็นรายจ่ายที่เด็กและเยาวชนมักต้องจ่าย ไม่ว่าจะเล่นที่บ้านหรือนอกบ้าน เช่น ค่าบัตรเติมเงินออนไลน์ ค่าหนังสือ คู่มือการเล่นเกมส์ เป็นต้น โดยมีค่าเฉลี่ยรายจ่ายดังนี้ - ค่าต่ออินเทอร์เน็ตบ้านเฉลี่ย 18.97 บาทต่อวัน หรือประมาณ 500-600 บาทต่อเดือน - ค่าบริการของร้านอินเทอร์เน็ตเฉลี่ย 35.04 บาทต่อวัน - จำนวนเงินที่ใช้ในการเล่นเกมส์จากตู้หยอดเหรียญเฉลี่ย 41.67 บาทต่อวัน - ค่าใช้จ่ายในการเช่าเครื่องเล่นเกมส์ เช่น เพลสเตชั่นเฉลี่ย 50.00 บาทต่อวัน - ค่าบัตรเติมเงินของเกมส์ออนไลน์เฉลี่ย 113.50 บาทต่อวัน - ค่าขนม น้ำอัดลม ระหว่างเล่นเกมส์เฉลี่ย 27.31 บาทต่อวัน - ค่าบุหรี่ ระหว่างเล่นเกมส์เฉลี่ย 20.50 บาทต่อวัน - ค่าหนังสือ หรือ CD ข้อมูลการเล่นเกมส์เฉลี่ย 82.50 บาทต่อวัน - ค่าโทรศัพท์คุยถึงการเล่นเกมส์กับเพื่อนเฉลี่ย 22.50 บาทต่อวัน ผลการศึกษาปัจจัยกระตุ้นพบว่า เด็กและเยาวชนติดเกมส์มากขึ้นเนื่องจากปัจจัยทางด้านพฤติกรรมและปัจจัยกระตุ้นภายนอก ปัจจัยด้านพฤติกรรมเกิดจากความสนุกสนาน เพลิดเพลินในการเล่นเกมส์ เบื่อ ว่าง ไม่รู้จะทำอะไร ได้ฝึกสมอง เกมส์น่าสนใจ สมจริง สวยงาม เทคโนโลยีทันสมัย คนเล่นกันเยอะ หาที่เล่นได้ง่าย ได้ระบายความเครียด หงุดหงิด เล่นตามเพื่อน/คนใกล้ตัว ฯลฯ และปัจจัยภายนอกเกิดจาก (1) ปัจจัยทางด้านสังคม เกิดจากการมีร้านเกมส์ในบริเวณที่พักอาศัย และเด็กและเยาวชนมักใช้เวลาว่างอยู่กับเพื่อนที่ติดเกมส์ (2) ปัจจัยทางด้านครอบครัว เกิดจากการมีเวลาอยู่กับครอบครัวน้อย และการขาดการควบคุมจากผู้ปกครอง (3) ปัจจัยทางด้านเศรษฐกิจ เกิดจากการมีรายได้เพียงพอที่จะใช้จ่ายและนำไปเล่น (4) ปัจจัยทางด้านจิตวิทยา เกิดจากความเครียดที่เกิดขึ้นกับเด็กและเยาวชน และวิธีการระบายความเครียด โดยสาเหตุที่สำคัญที่สุดที่ทำให้เล่นเกมส์ของเด็กและเยาวชนติดเกมส์ส่วนใหญ่ คือ เพื่อนชวนให้เล่น คิดเป็นร้อยละ 43.00 ของเด็กและเยาวชนติดเกมส์ทั้งหมด รองลงมา คือ ที่บ้านมีคอมพิวเตอร์หรือเกมส์ คิดเป็นร้อยละ 20.00 ของเด็กและเยาวชนติดเกมส์ทั้งหมด และเล่นเพราะเห็นคนอื่นเล่น คิดเป็นร้อยละ 13.67 ของเด็กและเยาวชนติดเกมส์ทั้งหมด ตามลำดับ สรุปประเด็นปัญหาที่ส่งผลให้เด็กและเยาวชนติดเกมส์ ได้แก่ ปัญหาทางครอบครัว การพัฒนาเทคโนโลยีและสื่อยั่วยุต่าง ปัญหาการแบ่งเวลาไม่ถูกต้องของเด็กและเยาวชน การเติบโตของธุรกิจการให้บริการจากร้านเกมส์ ร้านอินเทอร์เน็ต และตู้เกมส์ การเลือกคบเพื่อน และนิสัยส่วนตัว แนวทางการแก้ไขที่ได้จากตัวแทนครูอาจารย์ ผู้ปกครอง และนักเรียนนักศึกษา คือ ผู้ปกครอง และครู ควรให้การอบรมเลี้ยงดูและเอาใจใส่อย่างใกล้ชิด ให้เด็กและเยาวชนใช้เวลาว่างไปกับการทำกิจกรรมที่สร้างสรรค์ ปลูกฝังให้คิดเป็น เลือกเป็น ปฏิเสธเป็น และเอาใจใส่ติดตามพฤติกรรมที่เปลี่ยนแปลงอย่างใกล้ชิด ส่วนภาคธุรกิจเอกชนไม่ควรพัฒนารูปแบบของเกมส์ให้มีเนื้อหารุนแรง และสำหรับภาครัฐควรเข้มงวด จริงจังกับบทลงโทษของมาตรการต่างๆ ในการให้บริการร้านเกมส์ต่างๆ คำสำคัญ: การวิเคราะห์พฤติกรรม พฤติกรรมการใช้จ่ายเงิน เด็กและเยาวชน การติดเกมส์ Presently, the problems of game addiction in child and youth groups have grown more severe and become more complicated. Children and teenagers spend more and more money for game playing. Many game addicted youth sneak out of their home to play games at various game shops and become at risk of falling victim to the villains. This case study was intended to understand the behaviour of the game addicted child and youths in spending for game playing, to identify the factors encouraging these groups to spend more for playing games, and to discern the social and external environments attributable to the problems as well as propose the remedial measures to deal with excessive game playing and money spending of those youths. Covered in this study were 1,000 samples of 10-22 year-old adolescents which can be distinguished into 300 game addicts and 700 non-addicts to games, and another 50 samples inclusive of parents/guardians, game shop owners, academics, and social and human development workers. The research methodologies included questionnaire interviews for information, and data processing and analysis using descriptive statistics and Chi-square Test. Findings on the spending behaviour of game addicted child and youth groups revealed that the size of expenses depended largely on the mode of game playing. Those playing game at home via internet would spend about 500-600 per month or 19 baht per day. However, by playing game at the game shops, ones had to pay extra for service fee, snack, beverage, and cigarette. Furthermore, the game players whether playing at home or at the game shops had to spend money for buying pre-paid or call time refill card for online connection, books, and game playing handbooks, etc. On the average, a game addicted child and youth appeared to spend for different items or things as follows: - internet connection at home, 18.97 baht per day or 500-600 baht per month. - service fee of the internet shop, 35.04 baht per day. - money for playing games in coin-operated machines, 41.67 baht per day. - rental fee for such game machines as play station, 50.00 baht per day. - spending for online game prepaid card, 113.50 baht per day. - spending for snack and beverage consumption while playing games, 27.31 baht per day. - cost of cigarette smoking while playing games, 20.50 baht per day. - buying books or CD concerning game playing, 82.50 baht per day. - cost of telephone call to chat with friends about game playing, 22.50 baht per day. Findings on factors encouraging the spending for playing games showed that the game addicted child and youths were found to get hooked on game playing due to the personal behaviour factors and the external factors. The personal behaviour factors were due to the fun and enjoyment from game playing. They have free time and do not know what to do. They feel bored and can exercise one’s brain by playing games. The games are attractive, realistic, interesting features, popular, high technology, and easy to find game playing places. Most of all they play games to release stress, uneasiness, and play games following friends/acquaintance. External factors were first, social factors were due to the game shops are available nearby and the use of leisure time with game addicted friends. Second, family factors were due to the lack of time to spend with family and the lack of some attention from parents. Third, economic factors were due to an excessive income to spend for playing game. Fourth, psychology factors were due to the stress that they have and they want to release stress. The most important inductive factor causing the majority of game-addicted child and youth to start playing games was found to be persuasion from friends (43.00% of all game addicts under study), followed by availability of computer or games at home (20.00%), and demonstration effect from other game players (13.67%), respectively. Conclusions on the situation contributive to game addiction in child and youths are family problems, development in technologies and tempting media, improper allocation of leisure time of the child and youth, game shop, internet shop, and game machine servicing businesses, and personal psychological background of the children/ youths. Remedial Approaches which information were gathered from teachers, parents, and students are those who involved in taking care of children like parents and school teachers should pay close attention and give correct advice to them, encourage them to allocate their time for creative activity, inculcate them to learn how to think, how to choose, and how to say no concerning their friends, and pay close attention to monitor behavioral changes in the child and youth and spend more time with them. For business sector, forms and content of games should be developed carefully not to be overly violent nor highly realistic. For government sector, state agencies should be strict in implementing the punishments stipulated in various measures to reduce problems that may occur in the child and youth. Keywords: Behavior Analysis, Paying Behavior, Child and Youth Group, Game Addiction